Validation of the Spanish Version of the Trauma and Loss Spectrum Self-Report (TALS-SR): A Study on Healthcare Workers Facing the COVID-19 Pandemic - Carmassi C; Pedrinelli V; Antonini C; Dell'Oste V; Gravina D; Nardi B; Bertelloni CA; Massimetti G; Nieto-Munuera J; Dell'Osso L (Neuropsychiatric Disease and Treatment, 2023)
Claudia Carmassi,1 Virginia Pedrinelli,1,2 Corinna Antonini,1 Valerio Dell’Oste,1,2 Davide Gravina,1 Benedetta Nardi,1 Carlo Antonio Bertelloni,1 Gabriele Massimetti,1 Joaquín Nieto-Munuera,3 Liliana Dell’Osso1 1Department of Clinical and Experimental Medicine, University of Pisa, Pisa, Italy; 2Department of Biotechnology, Chemistry and Pharmacy, University of Siena, Siena, Italy; 3Department of Psychiatry and Social Psychology, University of Murcia, Murcia, SpainCorrespondence: Virginia Pedrinelli, Department of Clinical and Experimental Medicine, University of Pisa, Via Roma 67, Pisa, 56100, Italy, Tel +39 050 2219760, Fax +39 050 2219787, Email virginiapedrinelli@gmail.comBackground: The present study aimed at reporting about the validity and reliability of the Spanish version of the Trauma and Loss Spectrum-Self Report (TALS-SR), an instrument based on a multidimensional approach to Post-Traumatic Stress Disorder (PTSD) and Prolonged Grief Disorder (PGD), including a range of threatening or traumatic experiences and significant losses, besides the spectrum of peri-traumatic stress reactions and post-traumatic stress symptoms that may occur.Methods: A sample of 87 Health Care Workers (HCWs) employed in the COVID-19 Emergency Department at the Virgen de la Arrixaca and Reina Sofia Hospitals (Murcia, Spain) during the pandemic, was consecutively recruited and fulfilled the TALS-SR. Assessments also included the Impact of Event Scale-Revised (IES-R), to examine post-traumatic stress symptoms and probable PTSD. Nineteen HCWs fulfilled the TALS-SR again after three weeks from baseline for test–retest reliability.Results: This study provides evidence of good internal consistency and test–retest reliability of the Spanish version of the TALS-SR. Strong support for the internal validity structure was obtained, with positive and significant correlations between the five symptomatologic domains and the symptomatologic total score. Significant and good correlations between the TALS-SR symptomatologic domains and the IES-R total and single domains’ scores were found. The Questionnaire also demonstrated to discriminate between subjects with and without PTSD, with subjects with PTSD showing significantly higher mean scores in each domain of the TALS-SR.Conclusion: This study validates the Spanish version of TALS-SR, providing a useful instrument for a spectrum approach to PTSD and confirms the potential utility of this psychometric tool in both clinical practice and research settings.Keywords: mental health, stress disorders, traumatic, PTSD, psychological distress, health personnel, psychological tests